Writing About Byzantium : The History of Niketas Choniates - Urbainczyk, Theresa (Birmingham Byzantine and Ottoman Studies, 2017)
"Cover" -- "Title" -- "Copyright" -- "Dedication" -- "Contents" -- "Acknowledgements" -- "1 The puzzle of the History of Niketas Choniates" -- "2 âA history for workers and womenâ: statements of intent in the preface" -- "3 The world of Byzantine women" -- "4 Hellenism and classicism in the History" -- "5 The influence of the Old Testament" -- "6 Niketas on the emperors" -- "7 Conclusion" -- "Appendix 1: Addresses to the reader" -- "Appendix 2: Niketasâ flawless heroes".